Three-dimensional analysis of the proximal radial shaft and its intramedullary canal: a cadaver imaging study - Johannes M. Sieberer, MS; Michael Cobo, BS; Albert L. Rancu, BS; Julia LaMonica, MD; Kelsey Brennan; Lynn E. Copes, PhD; Steven M. Tommasini, PhD; Daniel H. Wiznia, MD; Lisa L. Lattanza, MD (JSES International, 2025)
Background: The proximal radius (PR) spans from the radial head (RH) to the bicipital tuberosity. Numerous studies have described this morphology. However, much of the existing work oversimplifies the morphology; for example, modeling the radial neck and/or tuberosity as cylinders, excluding the intramedullary canal (IC) from analysis, and basing models on two-dimensional imaging. The IC is important for radial arthroplasty implant stem selection. The purpose of this study is to quantify the morphology of the PR with a focus on the IC, utilizing the analysis of 3-dimensional models. We stratify the study population into age, sex, and height groups to capture the variance expected in the general population. We hypothesize that IC morphology differs significantly between age, sex, and height groups. Methods: One hundred fifty-one three-dimensional models of the PR and the corresponding ICs were created from CT scans of adult females and males with average height, divided into 3 equally sized age groups (25-30, 40-45, and 60-65 years), and adult females and males of short and tall built. The cross-sections of the first 60 mm of each PR shaft distal to the RH were automatically fitted with ellipses encompassing the external proximal radius (EPR) and the IC at 0.1 mm intervals. From this dataset, we quantified anatomical features relevant for RH arthroplasty, describing the PR and its IC. Results: Females had a smaller and narrower geometry. The PR morphology changed with age and patient height. The PR is eccentric, with the IC being significantly more eccentric. Conclusion: This study finds a wide range in positioning and width of specific anatomical features of the radius relevant to RH arthroplasty implant sizing, which might impact future development of RH implant stems. Furthermore, we found differences related to sex, age, and height of the patient. Both the PR and its IC are eccentric.